2016
DOI: 10.1186/s40064-016-3460-2
|View full text |Cite
|
Sign up to set email alerts
|

Robust watermark technique using masking and Hermite transform

Abstract: The following paper evaluates a watermark algorithm designed for digital images by using a perceptive mask and a normalization process, thus preventing human eye detection, as well as ensuring its robustness against common processing and geometric attacks. The Hermite transform is employed because it allows a perfect reconstruction of the image, while incorporating human visual system properties; moreover, it is based on the Gaussian functions derivates. The applied watermark represents information of the digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Our results with geometric attacks also show that the watermark resisted most of them, the worst case being Lena image under a scaling attack, with only 13 out of 16 satisfactory detection instances. Comparison with other methods demonstrated that using Hermite Transform is a good way to improve watermark algorithms, as we can review in [12,30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results with geometric attacks also show that the watermark resisted most of them, the worst case being Lena image under a scaling attack, with only 13 out of 16 satisfactory detection instances. Comparison with other methods demonstrated that using Hermite Transform is a good way to improve watermark algorithms, as we can review in [12,30].…”
Section: Discussionmentioning
confidence: 99%
“…A solution is the use of central geometric moments, as proposed in different researches [18,26]. In this work, we suggest achieving robustness to geometric attacks by normalizing the image before embedding the mark [12]. We aim at obtaining the necessary parameters to create a normalized template with intensity values up to 255.…”
Section: Image Normalizationmentioning
confidence: 99%
See 2 more Smart Citations